Elevational Diversity Patterns of Green Lacewings (Neuroptera: Chrysopidae) Uncovered With DNA Barcoding in a Biodiversity Hotspot of Southwest China - Lai, Yan; Liu, Yunhui; Liu, Xingyue (Frontiers in Ecology and Evolution, 2021)
Elevational diversity pattern can reflect the responses of biodiversity to climate change spatially. We aim to investigate the species diversity patterns of green lacewings (an important predatory group of insects) along the gradient of elevation from the Shaluli Mountains, which belong to the Hengduan Mountains in southwestern China, one of important hotpots of global biodiversity. We combined multiple approaches, including Automatic barcode gap discovery (ABGD), Assemble species by automatic partitioning analysis (ASAP), General Mixed Yule Coalescent (GMYC), Poisson tree processes (bPTP), Multi-rate poisson tree processes (mPTP), to delimit green lacewings species based on the stand barcoding region of COI. The α-diversity and β-diversity patterns of green lacewings from the Mts. Shaluli along the gradient of elevation were analyzed, with further exploration on how the temperature effect elevational-diversity pattern on broad-scale (county scale) elevational gradients. The DNA barcoding reference library consisted of 40 green lacewing species from the Mts. Shaluli. The α-diversity of green lacewings decreased with increasing elevation. Temperature was found to have significant effect on abundance and Shannon-Wiener diversity index but not on species richness. Nestedness replaced turnover as the main component of Sørensen dissimilarity with the increasing elevation, and greater nestedness occurred at low temperature area. The combination of reliable DNA barcoding database could improve the accuracy and efficiency to investigate the species diversity patterns of green lacewings. Temperature, resource and resultant interspecific competitions may have important roles in explaining the species diversity patterns of green lacewings from Mts. Shaluli. Priority of conservation should be given to the species at low elevation, middle elevation and relatively high temperature regions under the background of global climate warming.